Sekilas Tentang Wanita Dalam Perspektif Susastra Hindu - I Ketut Subagiasta (Mudra Jurnal Seni Budaya, 2007)
Woman is the main part of human life. People often talk about woman that is very much concerned in the community. However, woman can not be positioned trivially without respecting her own dignity and prestige. Woman ought to be positioned at a special honor, merit, and harmonious role. Woman should not be discredited, but empowered according to her proportional and natural feminine characteristic. In Hindu literatures, woman is described in several manuscripts like Manawadharmasastra, Itihasa, especially the epics of Mahabharata, Ramayana and other literatures.